Teknologi Papan Keseimbangan Untuk Latihan Pengendalian Stabilitas Postural Tubuh Anak - Putra Wisnu Agung Sucipto; Seta Samsiana; Arya Gilang Permana (Jurnal Ilmiah Fisioterapi, 2022)
On children , develop and repair condition motor is method best for realize balance postural. The method is with give a number of exercise which support strengthening performance muscle and coordination system sensory which complex . exercise this working for trigger movement psychomotor which emphasize on response physical in the form of movement body . To can support exercise balance body child , make it a technology which adopt principles in game child which used in stimulate movement psychomotor for control postural body . development technology done with method make a number of equipment , that is equipment technology game virtual and board balance electronic . From results design technology the succeed created a technology board balance for exercise control stability postural body child , which consist from board balance electronic and a game virtual as well as a data banking system capable keep history training . Based on results testing , tool this capable detect four direction motion tilt that is motion tilt forward , to the right , to the left and to the back . However tool this no can detect two direction tilt by together .